An evaluation of the factors that affecting the job satisfaction and relationship between job satisfaction and organizational commitment in education industry. - Chong, Pao Ni; Kah, Ka Yin; Law, Pik Yee; Tee, Cian Sin; Tey, Sin Ling (2011)
This study was designed to investigate the relationship between job satisfaction and factors such as pay and benefits, stress and training. At the same time, the study also designed to investigate the relationship between job satisfaction and organizational commitment. Specifically, the study sought to achieve the following: (1) to determine secondary school teachers‘ job satisfaction; (2) to find out what cause the job satisfaction of secondary school teacher; (3) to determine the relationship between the increasing number of teachers and factor such as pay and benefits, stress and training; (4) to find out the relationship between job satisfaction and organizational commitment. Data are collected from secondary sources and questionnaires distributed by researchers. Statistical Package for the Social Science (SPSS) version 16.0 is used to conduct new findings in the relationship of job satisfaction and factors such as pay and benefits, stress, training as well as organizational commitment.